Las firmas digitales en proceso de afiliación y su impacto en área comercial en empresa adquirente, Lima - Perú - Rodas Arrieta, Víctor Hugo (2016)
This investigation focuses on the activities of organizations which core business is delivering payment services through credit cards, which are called acquirers businesses, and the analysis of the actions taken by the business area of the company to recruit stores or institutions wishing to accept other different ways of payment other than cash. It will also evaluate and demonstrate the problems generated in the course of affiliation and that is mainly due to the contractual documentation necessary to complete this process of affiliation between the acquirer and the store or institution that wants to have the service.